THE READINESS OF FUTURE FOREIGN LANGUAGE TEACHERS TO SELF-EDUCATION ACTIVITY: THE THEORETICAL METHODOLOGICAL SUBSTANTIATION - Chernihivska, Nataliia S. (Educological discourse, 2014)
The theoretical methodological substantiation of the readiness of future foreign language teachers to self-education activity was represented in the article. The new investigated definition “the readiness of future foreign language teachers to self-education activity” was given. The psychoeducational analysis made it possible to draw a conclusion that the foundations of the theoretical methodological principles are interconnected components of the intension and processing supply: content, forms and methods of the students’ training for the self-education activity which are effective under diversified university conditions. The subsequent scientific investigations should be directed on approaches and methods of professional subjects teaching to force the students to self-education activity.